Culture Hybridity in Padi Lapa Temple, Jakarta - Azizi, Haikal Hibatul; Hartati, C. Dewi (Bambuti, 2019)
Abstract. Padi Lapa temple is located in west Jakarta. It is different with the other temple. The peak time for this temple is Thursday night. Thursday night is considered sacred time for people who often come here. In this temple there is a special offering place for Wali Songo which is only open on Thursday night. There is one statue that is above the altar, the statue is a statue of the grandson of Sunan Gunung Jati, Prabu Siliwangi, who is depicted as a tiger. The offerings is like Kejawen such as lisong, seven forms of flowers and incense. Special rituals were preserved. It can be seen that the tumpengan is seen on Eid al-Fitr, Eid al-Adha and the Prophet's birthday which are usually equated with the night of one sura. In the evening, a heirloom object that is placed or donated to the temple is sanctified by a pilgrim who studies or has sufficient Islamic knowledge.